Best Linear Unbiased Interpolation, Distribution, and Extrapolation of Time Series by Related Series - Chow, Gregory C.; Lin, An-loh (The Review of Economics and Statistics, 1971)
Gregory C. Chow, An-loh Lin, Best Linear Unbiased Interpolation, Distribution, and Extrapolation of Time Series by Related Series, The Review of Economics and Statistics, Vol. 53, No. 4 (Nov., 1971), pp. 372-375